Pengaruh Terpaan Iklan Product Placement Tropicana Slim dalam Drama Korea Castaway Diva terhadap Minat Beli Followers akun X @kdrama_menfess - Dinar Andira Pramesti Nur Rafifah; Firdaus Yuni Dharta; Fardiah Oktariani Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine how much influence the exposure of product placement advertisements in the Korean drama Castaway Diva has on the purchase interest of Tropicana Slim followers of account X @kdrama_menfess. This study uses advertising exposure theory. The population of this study was followers of account X @kdrama_menfess with a sample drawing using a purposive sampling approach of 100 respondents. The data results were obtained through a google form link with predetermined criteria. The data analysis methods used in this study were descriptive statistical tests, classical assumption tests, multiple linear regression tests, T tests, F tests, and coefficient of determination tests. This study produced the answer that the intensity and duration of advertising exposure had a significant influence on purchase interest, while the frequency did not have a significant influence and there was a significant influence of exposure to product placement advertisements in the Korean drama Castaway Diva on the purchase interest of Tropicana Slim followers of account X @kdrama_menfess. This is proven by simultaneous testing (F) where the calculated F value is much larger than the F table (20.650>2.698) and the determination coefficient test is 0.373 or 37.3% while the rest is influenced by other variables that were not examined in the study.